Dialogues between feminist ethics and experiences of community social psychology - Estrada-Maldonado, Sandra; Lenta, María Malena; Di Iorio, Jorgelina (Revista Pesquisas e Práticas Psicossociais, 2019)
Abstract The article discuse, from a feminist ethic, research/intervention community practices that have women as participants of community devices and also as executors or operators thereof.In an exploratory-descriptive approach, and using the extended case methodology as a methodological tool, this article identify epistemological, ontological and methodological aspects in three experiences, two in Argentina and one in Mexico, wich are defined as community research/intervention, and developed by university research groups. The experience linked to commitment leads to ask about the political sense and not only to delimit the knowledge production in Community Social Psychology. Doing politics and doing academy in feminist way implies repolitizing the territories questioning the androcentric assumptions from which it continues to produce epistemological, ethical, political and social subalternity. It is concluded that the dialogue between feminisms and community psychologies favors the autonomic construction and the intersubjective relationships, as well as problematizing power-to-know ways.